CSR REPORTING AND XBRL STANDARD ALIGNMENT DECISIVE FOR THE FUTURE OF FINANCE AND ACCOUNTING - Fijałkowska, Justyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2014)
This paper concentrates on the current trend in companies reporting concerning the publication of a satellite report on CSR and the possibilities of its inclusion into XBRL system as one of the principal issues decisive for the future of finance and accounting. The necessity of a practical alignment of business with ICT is underlined. This work contributes to a more detailed understanding of the essence of CSR reporting and presentation of XBRL standard as the useful tool of reporting system. It underlines utilization of information and communication technology advances on the example of XBRL taxonomy.